Relationship Between the Number of Hip Abduction Performance With Contralateral Adduction in Side-lying and the Lateral Pelvic Shift Distance During One-leg Lifting - Do-eun Lee; Jun-hee Kim; Gyeong-tae Gwak; Young-soo Weon; Oh-yun Kwon (Korean Research Society of Physical Therapy, 2023)
Background: The gluteus medius (Gmed) plays a critical role in maintaining frontal plane stability of the pelvis during functional activities, such as one-leg lifting. Side-lying hip abduction (SHA) has been used as a dynamic test to evaluate Gmed function. However, the abduction force of the lower leg against the floor is not controlled during SHA. Therefore, hip abduction performance with contralateral adduction in the side-lying position (HAPCA) can be proposed as an alternative method to assess performance of hip abduction. If the number of HAPCA is related to the lateral pelvic shift distance, a new quantitative measurement for hip abductor function may be presented. Objects: This study aimed to investigate the relationship between the number of successful HAPCA and the lateral pelvic shift distance during one-leg lifting. Methods: Thirty healthy participants were recruited, and lateral pelvic shift distance was measured during one-leg lifting test using two-dimensional analysis. The number of successful HAPCA was counted when participants touched both target bars at the beat of a metronome. Results: There was a negative correlation between the number of HAPCA and lateral pelvic shift distance during one-leg lifting (r = -0.630, p < 0.05). The number of HAPCA accounted for 39.7% of the variance in the lateral pelvic shift distance during one-leg lifting (F = 18.454, p < 0.001). Conclusion: The number of successful HAPCA is significantly correlated with lateral pelvic shift distance during one-leg lifting. This finding suggests that HAPCA can be proposed as a new measurement for hip abductor performance and more research is needed on its relationship with hip abductor strength.